Pengembangan Manajemen Gudang Menggunakan Opportunity Solution Tree - Johanes Kevin Cahyadi; Indriati Njoto Wibisono (Jurnal Titra, 2023)
PT. Krakatau Karya Abadi is a startup company with a focus on building a network of agents who distribute fast moving consumer goods (FMGC). By launching an application called Super, to expand and facilitate customer transactions in shopping for products. In the distribution process, a warehouse is needed as a place to store products to meet consumer needs.In order to use the warehouse optimally, warehouse management is needed. Warehousing management itself is an arrangement for managing warehousing and distribution of goods so that the stored goods remain in good condition and are distributed in a timely manner, the specifications are appropriate, and of course the amount is correct. The research focuses on the logistics division on the problem of warehouse management activities. The proposed improvement in warehouse management is related to the determination and development of an inventory system.